Bài này cũng đơn giản thôi bạn à ...mình có thể post được 3 cách lun , thử cách 1 nhé
Bài 1:
[TEX]{\color{Blue} I=\int \frac{dx}{cos^3x}=\int \frac{1}{cosx}d(tanx)=\frac{tanx}{cosx}-\int tanxd\left ( \frac{1}{cosx} \right )=\frac{tanx}{cosx}-\int tanx.\frac{sinx}{cos^2x}dx \\\\ =\frac{tanx}{cosx}-\int \frac{1}{cosx}\left ( \frac{1}{cos^2x} -1\right )dx \\\\ =\frac{tanx}{cosx}+\int \frac{dx}{cosx}-\int \frac{dx}{cos^3x}=\frac{tanx}{cosx}+I'-I+C[/TEX]
Tính [TEX]{\color{Blue} I'=\frac{cosxdx}{cos^2x}=\int \frac{d(sinx)}{1-sin^2x}=\frac{1}{2}ln\left | \frac{1+sinx}{1-sinx} \right |+C[/TEX]
[TEX]{\color{Blue} \Rightarrow 2I=\frac{tanx}{cosx}+I' \Rightarrow I=\frac{1}{2}\left [ \frac{tanx}{cosx}+\frac{1}{2}ln\left | \frac{1+sinx}{1-sinx} \right | \right ]+C[/TEX]
nèk! nhưng dòng thứ 3 là sao z pạn ^^! mik chưa hiểu . Hic